(3LhGH eSCdI aj ZjHI GdEeGes - (3GdTQja GdeQJVj , CHh GdbGSe,J (B436 (3g` s ((3GdfLa s)
(3ChdgG (B:s
(3hHYO aEf GdeNGdajf dfG ai GdEYJbGO jJhgehf UYhHI GdcdGe YdjfG s
(3BNQgG (B:s
(3hRhGd GdCSHGH GdeGfYI ef GbGeJgG s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B278 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B81s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis